Perpetual transience: the socio-ecological marginalization of São Paulo’s peripheries: - Lerchs, Lucas; Stevens, Jeroen; Cavalieri, Chiara (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2024)
In times of growing social inequality and ecological emergency, inaccessibility to housing pushes poor populations to settle in fragile ecological reserves. Through empirical research in the southern periphery of São Paulo, this article addresses the confluence of these social and environmental crises by analysing how the everyday practices of marginalised communities produce far-reaching territorial transformations. Through three multi-scalar stories, it examines the transformative relationship between marginalised populations and ecologies through the changing temporality of a series of local inhabiting practices that evolve from improvised squatting and minimal landscape manipulation to permanent settlement structures and ecological transfigurations. The article explores different temporalities of inhabiting practices and compares how different levels of oppression generate different socio-ecological relations. These mutating socio-ecological relations - dependency, decay and socio-ecological marginalisation - offer a temporal reflection for understanding the double ’tragedy in the making’ epitomised by the socio-ecological marginalisation of São Paulo’s southern periphery, where nature and city collide.